QoS and Objective Performance Analysis of Triple Play Services over ADSL2+ (Asymmetric Digital Subscriber Line 2+) - Khamiss, Nasser N.; Abdullah, Sarah Ali (Nahrain University College of Engineering Journal, 2014)
This paper will test the ADSL2+ broadband access network that support Triple Play Services (voice, video and data) on last mile. Initial applications presented are entertainment video (video on demand VoD and multicast video IPTV), voice (VoIP), and best-effort data (e.g. web browsing, File sharing /downloading). The QoS guidelines and the objective performance recommendations are presented in this paper in the context of an end-to-end delay, jitter, and delay variation. The networks were tested for the cases when the network availability is 85.5%-93% (services is full at each homes at a time, 7-14.5% traffic in core links) and 25% (services is not full at each homes at a time, 75% traffic in core links) and are agnostic to access technology based on ADSL2+, services architecture, and implementation. As result, the advantages of the ADSL2+ can facilitate the local content management and reduce the content access cost by minimizing traffic loading of the outgoing link.